Prenylated flavonoids from Sophora flavescens inhibit mushroom tyrosinase activity and modulate melanogenesis in murine melanoma cells and zebrafish - Fan, Fenling; Chen, Lanqing; Chen, Caihong; Ang, Song; Gutkowski, Justin; Seeram, Navindra P.; Ma, Hang; Li, Dongli (Frontiers in Pharmacology, 2024)
Sophora flavescens, a traditional Chinese medicine for treating conditions associated with abnormal skin pigmentation, contains flavonoids with inhibitory effects on tyrosinase. However, their mechanisms of action and their modulatory effects on melanogenesis remain unclear. Herein, a group of prenylated flavonoids was identified from S. flavescens extracts and their inhibitory activities on tyrosinase were evaluated. The anti-melanogenesis effects of these prenylated flavonoids were investigated in cellular (with murine melanoma cells) and animal (with zebrafish) models. Prenylated flavonoids including isoanhydroicaritin (IAI), kurarinone (KR), and sophoraflavanone G (SG) were the major active constituents in S. flavescens extracts with anti-tyrosinase activity (IC50 = 0.7, 7.1, and 6.7 μM, respectively). Enzyme kinetic assays showed that IAI, KR, and SG had a mixed type of tyrosinase inhibition, supported by data from computational docking. Notably, KR at concentrations of 5 and 10 μM enhanced intracellular tyrosinase activity and stimulated melanin production in B16F10 cells, whereas SG and IAI did not exhibit significant activity. Further studies with the zebrafish model showed that IAI (80 and 160 μM) inhibited melanin biosynthesis by about 30.0% while KR (20 μM) stimulated melanogenesis by 36.9%. Furthermore, a zebrafish depigmentation model supported the anti-melanogenesis effect of IAI (80 and 160 μM) by 33.0% and 34.4%, respectively. In summary, IAI was identified as a tyrosinase inhibitor with an anti-melanogenic effect and KR was an enhancer for melanin production in B16F10 cells and zebrafish. Findings from the current study suggest that IAI and KR from S. flavescens may exert contrasting effects in the modulation of melanin production, providing important insights into the development of S. flavescens as a cosmeceutical or medicinal ingredient.